Factors Associated with the Presence of Bacteria (Escherichia Coli) in Food at Elementary Schools in Kota Baru District in 2025 - Puspa Ningrum, Windi Meidita; Eka Rini, Willia Novita; Rahmat, Andree Aulia; Halim, Raden (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Food safety in elementary schools is essential to protect the health of school-aged children. One important indicator of food contamination is the presence of Escherichia coli bacteria, which reflects inadequate hygiene and sanitation practices. Personal hygiene of food handlers and environmental sanitation conditions play a crucial role in determining the microbiological safety of snack foods sold in schools. Objective: This study aimed to analyze factors associated with the presence of Escherichia coli in snack foods sold at elementary schools in Kota Baru District in 2025. Methods: This study employed a quantitative research design with a cross-sectional approach involving 45 food handlers. Data analysis was conducted using univariate and bivariate analyses with the Chi-square test. Results and discussion: Microbiological examination showed that 9 food samples (20.0%) were contaminated with Escherichia coli. Most food handlers demonstrated poor personal hygiene (66.7%) and inadequate environmental sanitation (71.1%). Statistical analysis revealed a significant association between personal hygiene and the presence of Escherichia coli (p = 0.020), as well as between environmental sanitation and bacterial contamination (p = 0.042). Better hygiene practices and adequate sanitation were associated with lower contamination risk. Conclusion: Personal hygiene of food handlers and environmental sanitation are significantly associated with Escherichia coli contamination.